The Influential Factors of Anemia on Patients with Chronic Kidney Failures Receiving Hemodialysis in Sultan Agung Islamic Hospital Semarang - Rukmana, Dewi; Azam, Mahalul; Farida, Eko (Public Health Perspective Journal, 2022)
Anemia suffered by patients with kidney failures can be prevented with erythropoietin administration (EPO). The chronic kidney disease (CKD) is the global epidemic with an estimated prevalence of 14% in the United States of America and 5% in the world. This research analyzes the influential factors of anemia via erythropoietin administration (EPO) for kidney failure patients who also receive hemodialysis in Sultan Agung Islamic hospital, Semarang. This research used analytical observation with Cross Sectional design. The population and sample were from 162 participants (total sampling). The statistical results with path analysis showed the direct influences with significant value on erythropoietin, comorbid, creatine, and ureum. The result showed insignificant results on family support, obedience levels, and cognition levels. The result found indirect and significant influences on family support, levels of obedience, levels of cognition. The insignificant values were on the comorbid, creatine, and ureum. The results showed the influential matters for the patients with anemia and chronic kidney failures that received hemodialysis were creatine with p=0.000, family support with p=0.00, levels of obedience with p=0.000, and levels of cognition with p=0.000.